Effect of acclimation medium on cell viability, membrane integrity and ability to consume malic acid in synthetic wine by oenological Lactobacillus plantarum strains - Bravo Ferrada, Barbara Mercedes (2013)
Aims: The aim of this work was to evaluate the effect of acclimation on the viability, membrane integrity and the ability to consume malic acid of three oenological strains of Lactobacillus plantarum. Methods and Results: Cultures in the stationary phase were inoculated in an acclimation medium (Accl.) containing 0, 6 or 10% v/v ethanol and incubated 48 h at 28°C. After incubation, cells were harvested by centrifugation and inoculated in a synthetic wine, containing 14% v/v ethanol and pH 3 5 at 28°C. Viability and membrane integrity were determined by flow cytometry (FC) using carboxyfluorescein diacetate (cFDA) and propidium iodide. Bacterial growth and malic acid consumption were monitored in a synthetic wine during 15 days. In nonacclimated strains, the damage of bacterial membranes produced a dramatic decrease in microbial viability in synthetic wine. In contrast, survival of strains previously acclimated in Accl. with 6 and 10% v/v ethanol was noticeable higher. Therefore, acclimation with ethanol increased the cultivability in synthetic wine and consequently, the consumption of L-malic acid after 15 days of growth. Conclusion: Acclimation of oenological strains in media containing ethanol prior to wine inoculation significantly decreases the membrane damage and improves viability in the harsh wine conditions. The role of membrane integrity is crucial to warrant the degradation of L-malic acid. Significance and Impact of the Study: The efficiency of multiparametric FC in monitoring viability and membrane damage along with the malic acid consumption has a strong impact on winemaking because it represents a useful tool for a quick and highly reliable evaluation of oenological parameters.